EXISTING PROBLEMS IN INCREASING INVESTMENT ATTRACTIVENESS IN ENTERPRISES AND WAYS TO OVERCOME THEM - Shayakubov Shakhzod Shakabilovich (Ecomind Press, 2025)
The main issue of the work of the article is the development of scientifically based proposals and recommendations to increase the investment attractiveness of joint-stock companies. The implementation of the suggestions and recommendations presented in the research work can serve to further increase the processes of introducing foreign and local investments into joint-stock companies. The hypothesis of the research is to positively solve the problems of ensuring investment attractiveness by developing an investment strategy, to develop practical proposals based on the effective use of advanced foreign experiences in this field, and to scientifically substantiate the effect of dividend policy on increasing investment attractiveness.
Keywords: Innovative activity, innovative product, investment, investors, companies, investment risk, joint company, stock investment attraction.